Development of Village Administrative Data Management System Through PAPEDA (Village Population Administration Development Application) in Pitu Village, North Halmahera Regency - Ikram, R A D; Kahar, A M; ., Gusrizal (Politeknik Statistika STIS, 2025)
This study discusses the utilization of technology in managing village administrative data, improving public service systems, and providing base data for local government decisionmaking. Using qualitative methods for data collection and the SDLC Waterfall Model for system development, this research analyzes the benefits of PAPEDA (Aplikasi Pembangunan Administrasi Kependudukan Desa), an output of the Desa CANTIK program, on village administrative data management and public services. Based on the evaluation results using Black Box Testing and User Satisfaction Surveys, this study shows that technology utilization in villages positively impacts the community. The use of PAPEDA not only makes it easier for village officials to manage village administrative data but also accelerates the public service process in the village. Residents can access various administrative services online, anytime, and anywhere. Additionally, village monographs and stunting monitoring enable local governments to use them as a basis for development. However, uneven internet connectivity hinders technology utilization, emphasizing the need for local governments to improve internet infrastructure.